2018
DOI: 10.1111/1745-9133.12338
|View full text |Cite
|
Sign up to set email alerts
|

Does Treatment Quality Matter?

Abstract: Research Summary The Florida Department of Juvenile Justice has implemented a process to evaluate the treatment quality of interventions provided statewide in all long‐term residential programs. In the current study, we examine the predictive validity of this treatment quality component in the prediction of recidivism of youth (N = 2,397) who completed juvenile justice residential programs from July 1, 2013 to June 30, 2014. We use hierarchical linear modeling to assess the effects of treatment quality (as you… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(3 citation statements)
references
References 58 publications
(76 reference statements)
0
3
0
Order By: Relevance
“…In addition, individual-level information on specific services received within the facility, the duration/dosage of each service, nor the quality/fidelity of services provided were not available in the data. Such treatment components (fidelity, treatment quality, duration, dosage, whether services were appropriately matched to risk/needs assessment results) have been demonstrated as critical components in recidivism reduction among youth completing residential programs in Florida (Baglivio et al, 2021; Baglivio, Wolff, Howell, et al, 2018; Baglivio, Wolff, Jackowski, et al, 2018). However, we note that our purposive decision to use the R-PACT assessment just prior to release (therefore just prior to the beginning of the recidivism follow-up), by default controls for differences in services received during placement as that assessment is a snapshot of each youth’s risk/needs profile after services have been provided.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, individual-level information on specific services received within the facility, the duration/dosage of each service, nor the quality/fidelity of services provided were not available in the data. Such treatment components (fidelity, treatment quality, duration, dosage, whether services were appropriately matched to risk/needs assessment results) have been demonstrated as critical components in recidivism reduction among youth completing residential programs in Florida (Baglivio et al, 2021; Baglivio, Wolff, Howell, et al, 2018; Baglivio, Wolff, Jackowski, et al, 2018). However, we note that our purposive decision to use the R-PACT assessment just prior to release (therefore just prior to the beginning of the recidivism follow-up), by default controls for differences in services received during placement as that assessment is a snapshot of each youth’s risk/needs profile after services have been provided.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the effectiveness of evidence‐based practices and services more generally is contingent on the quality of their implementation (Lipsey, 2009). Prior research has demonstrated the importance of treatment quality and achieving proscribed dosages of interventions for reducing criminogenic risk and recidivism (Baglivio, Wolff, Howell, et al., 2018; Baglivio, Wolff, Jackowski, et al., 2018; Lipsey et al., 2010). DJJ does not maintain detailed information on prevention service fidelity; however, the significant reduction in system contact associated with program completion—a potential indicator of service dosage—in the present study reaffirms the previous finding.…”
Section: Discussionmentioning
confidence: 99%
“…The version of the SPEP tested in Arizona lacked the quality of service delivery component, which had not yet been developed and incorporated into the scoring at the time of the validation studies. As mentioned earlier, a separate analysis of the relationship of the ratings on only that component with risk-adjusted recidivism was conducted with Florida data from 56 residential programs (Baglivio et al, 2018). Statistically significant odds ratios were found for the relationships with risk-adjusted rearrest, reconviction, and reincarceration with the respective odds ratios all about 0.89.…”
Section: The Spep Assessment Schemementioning
confidence: 99%